AMILUM PREGELATIN DARI UBI JALAR SEBAGAI BAHAN PENGIKAT DALAM FORMULA TABLET EKSTRAK BUAH MENGKUDU (Pregelatinized Sweet Potatao Starch as Binder in Formulation of Morinda citrifolia Extract Tablet) - Supriyatna, Nana (Jurnal Hasil Penelitian Industri, 2016)
The research of pregelatinized sweet potato starch as a binder in tablet formulations has beenconducted. Pregelatinized starch prepared by heating sweet potato starch suspension with a concentrationof 30% in water at temperature 60, 65 and 70 oC. Pregelatinized starch were evaluated its flow propertiesand compressibility. The results showed the flow properties and compressibility were still lack. The test oftablet formulations are uniformity of weight, hardness, friability and disintegration time. The resultcompared to the Pharmacopoeia then Anova test. The result test met the requirements to Pharmacopoeiawhile Anova test there was a difference in terms of hardness, friability and disintegration time. Tablet withpregelatinized starch cooked at 70oC has a different value of hardness and brittleness with the other tabletsi.e. 4.5 kg/cm2 and 0.031%, While tablet with Star RX 1500 as binder has a different value of disintegrationtime from others 6.42 minutes.